EVALUATION OF ENGLISH TEACHING MATERIALS USED AT SD IT UMMI IN KOTA BENGKULU BASED ON KTSP (KURIKULUM TINGKAT SATUAN PENDIDIKAN) - Meri Lestari; Syahrial Syahrial; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2018)
The objectives of this study were: (1) To find out whether textbook used by second grade students at SD IT UMMI Kota Bengkulu fulfill the criteria of a good textbook. (2) To find out whether the English textbook used by second grade students at SD IT UMMI Kota Bengkulu relevant to KTSP curriculum. This research used descriptive qualitative content analysis as its research method. The data were collected from the English student book “Let’s Make Friends with English” for second grade students. The results showed that English textbook entitled “Let’s make friends with English” used by second grade students at SD IT UMMI Kota Bengkulu have fulfilled the criteria of a good textbook by achieving the Fair fulfillment. The textbook was categorized relevance to the KTSP curriculum, but the activities in the listening can be said irrelevant because they cannot cover the learning objectives in listening. It was then recommended that the teachers need to modify the tasks and activities on the textbook which did not fulfill the criteria of good textbook, especially in the area of accompanying materials (CD, Cassettes and pictures), language skill, and teach ability aspects.